Thinking conjuncturally about ideology, housing and English planning. (February 2020) - Inch, Andy; Shepherd, Edward
This article explores the value of Stuart Hall's approach to conjunctural analysis for examining the complex relations between ideology and planning. By 'thinking conjuncturally', we explore planning as a site where multiple social, economic and political forces coalesce; ideology is one of these forces whose role and influence must be tracked alongside others. To illustrate this, we draw on recent and ongoing planning reforms in England and their relationship with housing development. Highlighting the faltering role of a particular ideological formation in 'suturing together contradictory lines of argument and emotional investments' around housing and planning, this article draws attention to planning as a space where ideological struggle takes place within the frame of a broader, contingent cultural hegemony. This struggle may help to reaffirm that hegemony, but it can also open space for alternative visions to be articulated, with potential to transform dominant logics of planning, and reveal routes to practical and progressive action.